Experimental evidence of pathogenic role of IgG autoantibodies in IgA nephropathy. Issue 118 (March 2021) - Moldoveanu, Zina; Suzuki, Hitoshi; Reily, Colin; Satake, Kenji; Novak, Lea; Xu, Nuo; Huang, Zhi-Qiang; Knoppova, Barbora; Khan, Atlas; Hall, Stacy; Yanagawa, Hiroyuki; Brown, Rhubell; et al.
Abstract: Background: IgA nephropathy is thought to be an autoimmune disease wherein galactose-deficient IgA1 (Gd-IgA1) is recognized by IgG autoantibodies, resulting in formation and renal accumulation of nephritogenic immune complexes. Although this hypothesis is supported by recent findings that, in renal immunodeposits of IgA nephropathy patients, IgG is enriched for Gd-IgA1-specific autoantibodies, experimental proof is still lacking. Methods: IgG isolated from sera of IgA nephropathy patients or produced as a recombinant IgG (rIgG) was mixed with human Gd-IgA1 to form immune complexes. IgG from healthy individuals served as a control. Nude and SCID mice were injected with human IgG and Gd-IgA1, in immune complexes or individually, and their presence in kidneys was ascertained by immunofluorescence. Pathologic changes in the glomeruli were evaluated by quantitative morphometry and exploratory transcriptomic profiling was performed by RNA-Seq. Results: Immunodeficient mice injected with Gd-IgA1 mixed with IgG autoantibodies from patients with IgA nephropathy, but not Gd-IgA1 mixed with IgG from healthy individuals, displayed IgA, IgG, and mouse complement C3 glomerular deposits and mesangioproliferative glomerular injury with hematuria and proteinuria. Un-complexed Gd-IgA1 or IgG did not induce pathological changes. Moreover, Gd-IgA1-rIgG immune complexes injected into immunodeficient mice induced histopathological changes characteristic of human disease. Exploratory transcriptome profiling of mouse kidney tissues indicated that these immune complexes altered gene expression of multiple pathways, in concordance with the changes observed in kidney biopsies of patients with IgA nephropathy. Conclusions: This study provides the first in vivo evidence for a pathogenic role of IgG autoantibodies specific for Gd-IgA1 in the pathogenesis of IgA nephropathy. Highlights: IgG autoantibodies in IgA nephropathy (IgAN) bind galactose-deficient IgA1 (Gd-IgA1). IgG autoantibodies from IgAN patients form immune complexes with Gd-IgA1. Immune complexes injected into mice induce pathologic glomerular changes. Immune complex-altered gene expression in mouse kidneys resembles that in IgAN.